Discovery in the Pramesti Ulangun Dance: A Possibility for Innovation in the Form of Balinese Dance Creations - Suryani, Ni Nyoman Manik; Suartini, Ni Wayan; Parta, I Ketut (IJCAS (International Journal of Creative and Arts Studies), 2024)
This article is dedicated to exploring the novelty of Pramesti Ulangun as a Balinese dance. Pramesti Ulangun presents a new Balinese dance for entertainment purposes. However, as a new dance, some audiences in Bali still doubt that this dance is a new dance. The problems are: 1) How is the process of creating the Pramesti Ulangun dance? 2) What is the form of discovery in the Pramesti Ulangun dance? 3) What are the advantages of discovery in the Pramesti Ulangun dance? Qualitative approaches were used to carry out this research. All primary data were collected through observation and interviews with informants. The data set is strengthened by the data obtained from the literature study. All data were analyzed qualitatively by using dance creation process theory and reception theory. The results of the research show: 1) the Pramesti Ulangun dance was created starting from an exploration of the story in the kakawin Niti Sastra. The next stage was experimentation and motion improvisation based on the choreographer's understanding of the characteristics of the God character from kakawin Niti Sastra. This dance choreography was then formed and tested with the dancers with the help of composers and traditional Balinese gamelan musicians. After that, the final form of the Pramesti Ulangun dance choreography was tested by involving dancers, musicians, and the audience; 2) Discovery in the Pramesti Ulangun dance can be seen from the combination of costumes, make-up, choreography, music, story, and various movements; 3) The advantage of discovery in the Pramesti Ulangun dance is the formation of movements and the meaning of the tale message.Kebaruan dalam Tari Pramesti Ulangun: Sebuah Peluang Inovasi Seni Pertunjukan Kreasi Bali Abstrak Artikel ini didedikasikan untuk mengeksplorasi unsur kebaruan Pramesti Ulangun sebagai tarian Bali. Tari Pramesti Ulangun merupakan sebuah tari kreasi Bali yang baru untuk hiburan. Namun, sebagai sebuah tarian baru, sebagian penonton di Bali masih ragu jika tarian ini merupakan tarian baru. Permasalahannya adalah : 1) Bagaimana proses terciptanya tari Pramesti Ulangun?; 2) Bagaimana bentuk kebaruan dalam tari Pramesti Ulangun?; 3) Apa kelebihan kebaruan dalam tari Pramesti Ulangun?. Metode kualitatif telah digunakan untuk melakukan penelitian ini. Seluruh data primer dikumpulkan melalui observasi dan wawancara terhadap informan. Kumpulan data tersebut diperkuat dengan data yang diperoleh dari studi literatur. Seluruh data dianalisis secara kualitatif dengan menggunakan teori proses penciptaan tari dan teori resepsi. Hasil penelitian menunjukkan : 1) tari Pramesti Ulangun tercipta bermula dari eksplorasi cerita dalam kakawin Niti Sastra. Tahap selanjutnya adalah eksperimen dan improvisasi gerak berdasarkan pemahaman koreografer terhadap Tuhan dalam kakawin Niti Sastra. Koreografi tari ini kemudian dibentuk dan diuji-coba kepada para penari dengan bantuan komposer dan penabuh gamelan tradisional Bali. Setelah itu, dilakukan uji coba bentuk akhir koreografi tari Pramesti Ulangun dengan melibatkan penari, pemusik dan penonton.; 2) Kebaruan dalam tari Pramesti Ulangun dapat dilihat dari perpaduan kostum, tata rias, koreografi, musik, cerita dan berbagai gerak; 3) Keunggulan kebaruan dalam tari Pramesti Ulangun adalah terbentuknya formasi gerak baru dan makna pesan kisah mitologi.